1999
DOI: 10.1089/cbr.1999.14.31
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel (Taxol): An Inhibitor of Angiogenesis in a Highly Vascularized Transgenic Breast Cancer

Abstract: Paclitaxel (Taxol), a promoter of microtubule polymerization and a radiosensitizing agent, is one of the more active anticancer drugs in the current treatment of solid tumors. In this study, we show that paclitaxel possesses an antiangiogenic property associated with a down-regulation of vascular endothelial growth factor (VEGF) in a highly-vascularized transgenic murine breast cancer (Met-1). Paclitaxel, at non-cytotoxic doses of 0, 3 and 6 mg/kg/day, was administered intraperitoneally for 5 days to nude mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
73
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(76 citation statements)
references
References 6 publications
1
73
0
2
Order By: Relevance
“…Paclitaxel at low nanomolar concentrations can also affect tumor angiogenesis indirectly either by reducing the tumor secretion of angiogenic growth factors, such as VEGF (10) or by decreasing its secretion by endothelial cells, which may act in an autocrine fashion (Merchán and Sukhatme, unpublished findings). 5 Other possible mechanisms that may explain the antiangiogenic effects of this combination include a decrease in circulating endothelial precursor number and viability, as previously demonstrated with metronomic cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paclitaxel at low nanomolar concentrations can also affect tumor angiogenesis indirectly either by reducing the tumor secretion of angiogenic growth factors, such as VEGF (10) or by decreasing its secretion by endothelial cells, which may act in an autocrine fashion (Merchán and Sukhatme, unpublished findings). 5 Other possible mechanisms that may explain the antiangiogenic effects of this combination include a decrease in circulating endothelial precursor number and viability, as previously demonstrated with metronomic cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
“…Among these compounds are the microtubule-interfering agents vinblastine, paclitaxel and docetaxel. 3,[7][8][9][10][11][12][13][14] Paclitaxel is a microtubule-polymerizing agent that is widely used in the treatment of solid tumors. In addition to its known cytotoxic effects, it inhibits endothelial cell migration, invasion, capillary tube formation and proliferation in vitro at concentrations ranging from picomolar to nanomolar, depending on the endothelial cell type and the assay conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Microtubule-destabilising agents have been recently investigated as antivascular compounds (Iyer et al, 1998;Blakey et al, 2002), and an antiangiogenic potential has been reported for paclitaxel (PTX) and docetaxel (Belotti et al, 1996;Klauber et al, 1997;Lau et al, 1999;Schimming et al, 1999;Sweeney et al, 2001;Cassinelli et al, 2002). The antiangiogenic activity of PTX has been ascribed mainly to its ability to inhibit endothelial cell motility, rather than proliferation (Belotti et al, 1996) and to downregulate angiogenesis-related growth factors .…”
mentioning
confidence: 99%
“…Furthermore, for S phase-specific drugs, more frequent dosing may expose more cells to the drug during the sensitive phase of the cell cycle. In addition, the use of weekly paclitaxel may have additional anti-angiogenic effects when used in a fractionated schedule (Belotti et al, 1996;Lau et al, 1999).…”
Section: Discussionmentioning
confidence: 99%